TRANSFORMATION OF NATIONAL EDUCATION THROUGH THE INDEPENDENT CURRICULUM: POLICY ANALYSIS OF THE MINISTER OF EDUCATION, CULTURE, RESEARCH, AND TECHNOLOGY REGULATION NUMBER 12 OF 2024 AND THE CHALLENGES OF ITS IMPLEMENTATION AT VARIOUS EDUCATIONAL LEVELS (LITERATURE REVIEW METHOD) - Syamsu Qamar Badu; Novianty Djafri; Wilda Rizkiyahnur Nasution (Adisam Publisher, 2025)
This research aims to analyse the policy of the Minister of Education, Culture, Research, and Technology Regulation Number 12 of 2024 which establishes Merdeka Curriculum as the basic framework of national education, and identify the challenges of its implementation at various levels of education in Indonesia. The method used is a literature review with a descriptive qualitative approach, reviewing policy documents, scientific articles, and related research reports. The results of the analysis show that Merdeka Curriculum provides flexibility to education units and teachers in designing learning that is relevant to the needs of students and local conditions, and emphasises strengthening character through the Pancasila Student Profile. However, the implementation of this curriculum still faces significant challenges, such as limited facilities and infrastructure, human resource readiness, inequality of access in 3T areas, and the need for continuous training for teachers. The success of educational transformation through Merdeka Curriculum depends on the collaboration of all stakeholders and continuous efforts in capacity building, equitable distribution of facilities, and strengthening an inclusive and adaptive learning ecosystem.